2022
DOI: 10.3390/ijms23052531
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-Sparing Approaches in Atypical Endometrial Hyperplasia and Endometrial Cancer Patients: Current Evidence and Future Directions

Abstract: Endometrial cancer (EC) is the fourth most common cancer in women in developed countries. Although it is usually diagnosed in postmenopausal women, its incidence has increased in young women, as well in recent decades, with an estimated rate of 4% in those under 40 years of age. Factors involved in this increase, particularly in resource-rich countries, include delayed childbearing and the rise in obesity. The new molecular classification of EC should help to personalize treatment, through appropriate candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…Thus, women with obesity are less likely to undergo minimally invasive approaches and are at a much higher risk for developing postoperative complications (e.g., wound infection, venous thromboses, and prolonged length of stay ( 81 )). As obesity rates continue to rise and childbearing is increasingly deferred, growing numbers of endometrial cancer may be found in women desiring uterine preservation and progestin based therapies may be appropriate ( 82 ). Bariatric surgery is effective in achieving weight loss, restoring the hypothalamic–pituitary axis which is deranged in many of these women, and optimizing pregnancy outcomes ( 83 ).…”
Section: Bariatric Surgery and Endometrial Cancer Treatmentmentioning
confidence: 99%
“…Thus, women with obesity are less likely to undergo minimally invasive approaches and are at a much higher risk for developing postoperative complications (e.g., wound infection, venous thromboses, and prolonged length of stay ( 81 )). As obesity rates continue to rise and childbearing is increasingly deferred, growing numbers of endometrial cancer may be found in women desiring uterine preservation and progestin based therapies may be appropriate ( 82 ). Bariatric surgery is effective in achieving weight loss, restoring the hypothalamic–pituitary axis which is deranged in many of these women, and optimizing pregnancy outcomes ( 83 ).…”
Section: Bariatric Surgery and Endometrial Cancer Treatmentmentioning
confidence: 99%
“…Lynch syndrome is an inherited condition predisposing to colorectal cancer, EC, gastric cancer, and other malignancies, and accounts for 2 to 5% of all endometrial malig-nancies [29][30][31]. This autosomal dominant hereditary syndrome with high penetrance is caused by the mutation of a mismatch repair gene that is involved in DNA mismatch repair (MMR)/microsatellite instability (MSI): MLH1, MSH 2 or 6, and PMS2 [6]. It affects 1 out of 370 to 2000 persons in Western countries [32,33].…”
Section: Lynch Syndrome and Association With Concomitant Tumorsmentioning
confidence: 99%
“…In 2013, the Cancer Genome Atlas Research Network published a molecular diagnostic classification that defines four prognostic categories in endometrial cancer: POLE ultramutated, microsatellite instability hypermutated, low copy-number tumor, and high copynumber tumor [6,23,37].…”
Section: Biomolecular and Genetic Prognostic Factors In Endometrial C...mentioning
confidence: 99%
See 2 more Smart Citations